Development of In Vitro Bioengineered Vascular Grafts for Microsurgery and Vascular Surgery Applications. Issue 5 (May 2019) - Singh, Gurtej; Cordero, John; Wiles, Brody; Tembelis, Miltiadis N.; Liang, Kai-Li; Rafailovich, Miriam; Simon, Marcia; Khan, Sami U.; Bui, Duc T.; Dagum, Alexander B.
Abstract : Introduction: The use of vascular grafts is continuing to rise due to the increasing prevalence of coronary artery bypass grafting and microvascular flap-based tissue reconstructions. The current options of using native vessels (saphenous vein) or the synthetic grafts (Dacron) have been unable to manage current needs. In this study, we employed an original tissue engineering approach to develop a multi-layered vascular graft that has the potential to address some of the limitations of the existing grafts. Materials and Methods: Biomaterials, gelatin and fibrin, were used to develop a two-layered vascular graft. The graft was seeded with endothelial cells and imaged using confocal microscopy. The graft's architecture and its mechanical properties were also characterized using histology, Scanning Electron Microscopy and rheological studies. Results: Our methodology resulted in the development of a vascular graft with precise spatial localization of the two layers. The endothelial cells fully covered the lumen of the developed vascular graft, thus providing a non-thrombogenic surface. The elastic modulus of the biomaterials employed in this graft was found to be 5.186 KPa, paralleling that of internal mammary artery. The burst pressure of this graft was also measured and was found close to that of the saphenous vein (~2000 mm Hg). Conclusions: We were successfully able to employ a unique method to synthesize a multi-layered vascularized graft having adequate biological and mechanical properties. Studies are ongoing involving implantation of this developed vascular graft in the rat femoral artery and characterization of parameters such as vascular remodeling and patency.